2013
DOI: 10.1186/1479-5876-11-228
|View full text |Cite
|
Sign up to set email alerts
|

Functional effect of Saffron supplementation and risk genotypes in early age-related macular degeneration: a preliminary report

Abstract: BackgroundTo determine whether the functional effects of oral supplementation with Saffron, a natural compound that proved to be neuroprotective in early age-related macular degeneration, are influenced by complement factor H (CFH) and age-related maculopathy susceptibility 2 (ARMS2) risk genotypes.MethodsThirty-three early AMD patients, screened for CFH (rs1061170) and ARMS2 (rs10490924) polymorphisms and receiving Saffron oral supplementation (20 mg/day) over an average period of treatment of 11 months (rang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 48 publications
2
39
0
1
Order By: Relevance
“…In particular, orally administered saffron partially preserved both morphology and function in light damaged retina [1]. A pilot clinical trial conducted on AMD patients provided the first evidence of successful saffron treatment in therapy [11], the positive effects being maintained in time [12] and in patients carrying genetic mutation [13]. Multiple actions of saffron have been suggested, including modulation of gene expression in animal models of retinal degeneration [14].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, orally administered saffron partially preserved both morphology and function in light damaged retina [1]. A pilot clinical trial conducted on AMD patients provided the first evidence of successful saffron treatment in therapy [11], the positive effects being maintained in time [12] and in patients carrying genetic mutation [13]. Multiple actions of saffron have been suggested, including modulation of gene expression in animal models of retinal degeneration [14].…”
Section: Introductionmentioning
confidence: 99%
“…Maccarone et al [22] provided data showing that Saf is protective in a rat model of lightinduced retinal degeneration. A proof-of-principle clinical trial in age-related macular degeneration (AMD) patients confirmed the potentiality of Saf treatment in neurodegenerative diseases and its consistency in time [23,24] and in patients carrying genetic mutations [25]. The biological mechanisms underlying neuroprotection are thus far unknown even though a direct control of gene expression was suggested [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…; Marangoni et al . ), equating to a much lower daily dose (~ 0.25–0.33 mg/kg/day) than that used in this study. It is also possible that differences in the dose–response relationship arise when the daily dose of saffron is consumed as a single bolus (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The sustained neuroprotective efficacy of saffron following 10 days of pretreatment may relate to the daily dose given, which was estimated at 1 mg/kg/day (via injection of 0.2% saffronwater into a vegetable matrix) in the rat study compared tõ 14 mg/kg/day in this study. Similarly, in successful clinical trials of saffron in early-stage age-related macular degeneration, participants received 20 mg/day of saffron supplementation (Falsini et al 2010;Piccardi et al 2012;Marangoni et al 2013), equating to a much lower daily dose (~0.25-0.33 mg/kg/day) than that used in this study. It is also possible that differences in the dose-response relationship arise when the daily dose of saffron is consumed as a single bolus (e.g.…”
Section: Comparison To Previous Studies and Limitationsmentioning
confidence: 99%